Título Padrão: Hg mobilization fromn dredging - de Lacerda, Luiz Drude; Belmino, Ingra Kellen Belmino; Moreira, Lucas Buruaem; Marins, Rozane Valente (Arquivos de Ciências do Mar, 2020)
Dredging and tailings disposal can mobilize mercury (Hg) accumulated in bottom sediments, increasing the exposure of the aquatic biota. In the Mucuripe Harbor, NE, Brazil, dredging is performed regularly, but the impact on Hg mobilization is unknown. This paper presents results from the monitoring of a dredging operation to characterize and quantify an eventual Hg mobilization. The results showed that remobilization is significant and is associated with suspended solids. Further deposition of the Hg-enriched, remobilized, suspended solids increased Hg concentrations by a factor of 1.2 and 2.0 in harbor and shelf sediments, respectively. Maximum concentrations in harbor and shelf sediments reached 79.9 ng.g-1 and 32.4 ng.g-1 (20 and 9 higher than the regional background, respectively). The progressive increase in Hg concentrations may result in higher exposure to the local biota. Keywords: metals, mobilization, contamination, coastal sediments.